ANALISIS KINERJA KEUANGAN ANGGARAN PENDAPATAN DAN BELANJA DESA DI KANTOR PEMERINTAH DESA BANDAR JAYA KECAMATAN SEKAYU - Irfansyah, Ahmad (Jurnal Ilmiah Akuntansi Rahmaniyah, 2025)
This study aims to analyze and describe financial performance at the Bandar Jaya Village Government Office, Sekayu District, Musi Banyuasin Regency in terms of Village Budget Realization (APBDes). The data used in this study was data for fiscal year 2021-2023. The data collection techniques used in this study are interviews conducted by village heads and village office staffs related to the financial management of the Bandar Jaya Village Office and documentation in the form of financial documents, in the range of year 2021-2023 Bandar Jaya Village Office Budget Realization Report. In results showed that the overall financial performance of the village in the Bandar Jaya Village Government Office, Sekayu District, Musi Banyuasin Regency could be categorized as economic, but inefficient and ineffective.